PENGARUH BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT YALE SETYA SENTOSA - Taqwa Putra Khatulistiwa; Hery Sawiji; Tutik Susilowati (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2021)
This research was conducted based on the findings that emerged, namely the decline in the performance of PT Yale employees as indicated by the furniture production carried out; the majority of employees do not understand organizational culture; employees are less innovative; employee motivation drops. This study aims to determine: (1) the influence of organizational culture on employee performance at PT. Yale Setya Sentosa. (2) the influence of work motivation on employee performance at PT. Yale Setya Sentosa. (3) the influence of organizational culture and motivation jointly influence the performance of employees of PT Yale Setya Sentosa. This research is a quantitative correlational study with a descriptive approach. The sampling technique used was purposive sampling. Data collection techniques used were interviews and questionnaires, namely by providing structured statements to respondents designed to obtain precise and accurate information. Prior to the hypothesis testing, assumptions were tested, namely normality test, multicollinearity test and heteroscedasticity. The data analysis technique used is multiple linear regression analysis, t test, F test and R quadrad test. The results showed that: 1) Organizational culture affects the performance of employees of PT Yale Setya Sentosa. 2) Employee work motivation affects the employee performance of PT Yale Setya Sentosa. 3) Organizational culture and motivation jointly influence the performance of employees of PT Yale Setya Sentosa